RASISME DALAM NOVEL THE KITE RUNNER - Muhammad Fakhran al Ramadhan (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2021)
Racism is rooted from colonial era that the colonizer considers their race that is different and higher than others. It produces social inequality between colonizer and their colonized. The Kite Runner depicts the story of life in Afghanistan in the middle of the tribal conflicts and war; Hazaras, the minority ethnic group genocide done by the Pashtun, the majority, children and women rapes, and civilians slaughter by Taliban. In the middle of the war, live two main characters, Amir and Hassan, ten years old boys who come from different social class yet living in the same roof. They both have the same father without their knowing, but with different mix of race. Different race and social class results in discriminative acts not just between the two of them but also among society. This research aims to analyze and find out how The Kite Runner depicts the racism in Afghanistn during 1970s up to 2001. Pashtun Taliban represented by Assef as the villain vs Pashtun, Amir as the main character. Pashtun vs Hazara is also known by the characters; Assef with Hassan, Amir and Hassan, Assef and Sohrab, Baba and Ali, Baba and Sanaubar. This research uses descriptive analytical method. This analysis is focusing on five aspects of racism, namely (1) discrimination, (2) segregation, (3) slavery, (4) prejudice, and (5) stereotype. It can be found that the discrimination is done by Amir and his Father, Baba who treat Hassan and Ali, who are from minority ethnic, as their slaves. Next is segregation and discrimination depicted by Assef, a young Afghanistan who praises Hitler and assumes that his ethnic is more decorous than others in Afghanistan and he tries to chase Hazara from Afghanistan. The slavery can be seen when Baba and Amir treats Ali and Hassan as their maid in their house. The prejudice can be seen when there are some Pashtun thinks of the hazrasa existence living together with Baba and Amir. From Prejudice, it results the stereotyping from other people of imagining the Hazara. The authoritarian government, Taliban, also show the mistreatment of racism to the Afghans. Afghans often get sexual harassment, being raped, or even being killed if the break the law of Taliban.